Interfacial, mechanical, and thermal behavior of PEI/glass fiber welded joints influenced by hygrothermal conditioning - Barbosa Marques, Luís Felipe [UNESP] (2022)
This work aims to characterize the influence of hygrothermal conditioning on the mechanical and thermal behavior as well as the fractographic aspects of the interface of poly(ether imide) and glass fiber composite joints welded by electrical resistance using 400 mesh of AISI 304 stainless steel. The composites were mechanically characterized by Lap Shear Strength (LSS) and End Notched Flexure (ENF) testing to investigate maximum shear stress and energy from mode II interlaminar fracture toughness. Fractography was performed by SEM, while the influence on glass transition temperature and working temperature were evaluated by Dynamic-Mechanical Analysis and thermogravimetry. In the conditioned samples, the mechanical properties reduced 23% in the LSS test and 28% in the ENF test, while the fractography studies revealed elements of interlaminar and intralaminar fracture in both conditions. Thermal properties did not change significantly to disqualify this composite when applied to welding.